Pengaruh Penggunaan Media Gambar terhadap Hasil Belajar Siswa pada Mata Pelajaran IPA Tentang Penggolongan Hewan Menurut Jenis Makanan di Kelas IV SDI Manumuti - Gisela Nana; Yuventius Tamelab; Damian Puling (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Thesis by Gisela Nana, Nim 2386206182 entitled “ The influence of the media images of the students learning in subjects IPA about animal classification according to the type of food in class IV SDI Manumuti Malaka District”. This research of this study is to determine the students learning outcomes after using picture media in science subject on animal classfication based of food types. The method used the quantitative descriptive method. This study was conducted in SDI Manumuti, Umanen Lawalu Village, District Malaka Tengah, District of malaka. Data collection technique is a test and analysis technique used are simple linear regression statistical analysis. From the results of the study prove that as many as 18 people or 99% of students gaining higt grades in learning outcomes, whereas 1 or equal to 1% less value in learning outcomes. It is evident from the results of test calculations of Fcount = 5,70 which is significantly larger than the Ftable at the significant level of 5% N= 18 at 4,49 or equal to Fcount ≥ Ftable or 5,70 ≥ 4,49. Based on the above results the value of Fcount is greater than Ftable namely Fcount = 5,70 and F table =4,49. Then Ho is rejected and Ha accepted. It can be concluded that there is the influence of the media images of the students learning in subjects IPA about animal classifacation according to the type of food in class IV SDI Manumuti Malaka District.